RANCANG BANGUN SISTEM MONITORING PROSES PEMBUATAN KOMPOS DARI SAMPAH RUMAH TANGGA BERBASIS INTERNET OF THINGS (IoT) - Diharja, Sasmita Prawira; Arimbawa, I Wayan Agus; Zubaidi, Ariyan (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2025)
Household waste is one of the largest contributors to environmental waste, reaching 39.63% of the total 19.45 million tonnes of waste produced in Indonesia in 2022 from National Waste Management Information System (SIPSN) data. Waste is a very serious environmental problem that continues to be faced by the government and society. The waste produced every year increases along with the increase in population. Making compost from household organic waste is one solution at the household level to reduce the impact of waste and provide organic fertilizer for plants. However, the main problem is the lack of waste processing and public awareness. As an alternative solution, the use of the Internet of Things (IoT) can be utilized. This research utilizes the NodeMCU ESP8266 and DHT11, MQ4 sensors and incandescent lamps to monitor and control the compost making process. Through integration with the Telegram bot, this system allows users to monitor and manage the process remotely, which in turn contributes to reducing waste, environmental pollution and providing organic fertilizer. In this study, the results obtained during the 15 day compost making process had an average temperature of 40.63, humidity 67%, and methane gas produced was less than 700 ppm. The odor produced during composting smells earthy and fragrant, has a brownish black color, and has a crumbly texture, softens easily, and experiences weight loss. From the characteristics above, it can be interpreted that the compost made has good quality.